Global surveillance of emerging diseases: the ProMED-mail perspective Vigilância global de doenças emergentes: a perspectiva da ProMED-mail - John P. Woodall (Cadernos de Saúde Pública, 2001)
The Internet is changing the way global disease surveillance is conducted. Countries and international organizations are increasingly placing their outbreak reports on the Internet, which speeds up distribution and therefore prevention and control. The World Health Organization (WHO) has recognized the value of nongovernmental organizations and the media in reporting outbreaks, which it then attempts to verify through its country offices. However, WHO and other official sources are constrained in their reporting by the need for bureaucratic clearance. ProMED-mail <www.promedmail.org> has no such constraints, and posts outbreak reports 7 days a week. It is moderated by infectious disease specialists who add relevant comments. Thus, ProMED-mail complements official sources and provides early warning of outbreaks. Its network is more than 20,000 people in over 150 countries, who place their computers and time at the network's disposal and report on outbreaks of which they have knowledge. Regions and countries could benefit from adopting the ProMED-mail approach to complement their own disease surveillance systems. A Internet está mudando a condução da vigilância global de doenças. Cada vez mais, os países e as organizações internacionais estão divulgando seus informes na Internet, o que acelera não apenas a distribuição desta informação, como também, consequentemente, a prevenção e controle das doenças. A Organização Mundial da Saúde (OMS) já reconheceu a importância das ONGs e da imprensa na notificação de surtos, que procura verificar posteriormente através de suas agências locais. Entretanto, a OMS e outras fontes oficiais sofrem restrições em seus relatórios pela obrigatoriedade da autorização burocrática, além de só publicarem informes nos dias úteis. A ProMED-mail <www.promedmail.org> não está sujeita a tais restrições. A rede é moderada por especialistas em doenças infecciosas, que acrescentam comentários relevantes. Assim, a ProMED-mail complementa as fontes oficiais e divulga alertas precoces relativos a surtos. Em mais de 150 países, a rede inclui mais de 20.000 profissionais, que colocam seus computadores e tempo à disposição da rede e notificam os surtos dos quais têm conhecimento. Regiões e países poderiam beneficiar-se da adoção do sistema ProMED-mail para complementar seus próprios sistemas de vigilância.